"Dni Gdańska" Zaproszenie. (Gdańsk : [wydawca nieznany], 1985)
Zaproszenie na sesję 10.08.1985 r.
Keywords: Drukarstwo -- Polska -- Głogów -- historia -- konferencje; Gdańsk (Polska) -- 1945-1990 -- druki ulotne; Zaproszenia -- 1970-2000.; Zaproszenie